PERUBAHAN PELAKSANAAN TRADISI BATOMBEDI NAGARI ABAI KABUPATEN SOLOK SELATAN - Wahyu Novsa Rahma Dani; Wimbrayardi (Universitas Negeri Padang, 2025)
This study aims to describe the changes in the implementation of the Batombe tradition in the past and present in Nagari Abai, South Solok Regency. This research is a qualitative descriptive study. The research instruments are the researchers themselves, assisted by writing tools and a camera. Data was collected through literature review, observation, interviews and documentation. The steps to analyse the data are data reduction, data presentation and drawing conclusions. The results show that the implementation of the Batombe tradition in Nagari Abai, South Solok Regency has experienced changes, which were previously carried out spontaneously and simply without stage arrangements and now appear more modern and organised, complemented by additional musical instruments, performance costumes, and the use of stage arrangements and sound technology. The factors causing changes in the practice of the Batombe tradition include the influence of globalisation on people's entertainment patterns, modernization as an effort for adaptation and preservation, shifts in the social values and functions of Batombe, changes in youth participation patterns, media, and the commercialization of traditional arts. The impacts of changes in the practice of the Batombe tradition consist of positive and negative effects. Positive effects can prolong the life of the tradition through adaptation to contemporary times, while negative effects involve the erosion of customary values and sacredness due to modernization, which means the displacement of customary values and sacredness that form the soul of the Batombe tradition.